The Increase Level of Muscle Adductor in Idiopathic Vocal Cord Adductor Paralysis Post Biofeedback Vocal Therapy - Rani Maharyati1, Irwan Kristyono1, Muhtarum Yusuf1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The Idiopathic Vocal Cord Adductor Paralysis (KAKVI) is the inability of muscle that moves the vocalist notochord to medial in phonation time with the idiopathic. This condition might has impact to the emerge of hoarse voice and other lamentations which are related to the voice production. The conventional voice therapy still show the number of the recovery of low dysphonia. Method: The diagnosis of KAKVI is based on the anamnesis, physical check up, thorax photograph and laryngoscopy fiberoptic and is conducted the measurement of vocalist cord adductor muscular construction strength before the BF voice therapy with equipments. Then, the BF voice therapy is conducted twice a week for four weeks. The voice exercise is continued in home once a day by patients themselves. The measurement of the strength of vocalist cord adductor muscle contraction is conducted after the BF voice therapy. Results: The result of the study revealed that there were KAKVI. The result of adductor muscular contraction strength with statistic examination in a short test is p = 0,044. . The result of statistic examination of long a is p=0,000. . The result of statistic test of count test is p=0,000. Therefore, the change of adductor muscular contraction strength on KAKVI after the BF voice therapy is found a significant increase (p < 0,05). Conclusion: This study revealed that there are an increase of adductor muscular contraction strength in KAKVI after the BF voice therapy.